Integração de padrões organizacionais e de processo ao método ágil Scrum - Costa Filho, Edes Garcia da (2006)
Due to the increasing importance of software in society, the software engineering area has devoted continuous effort to improve the software products development process. Today, even with the technological progress, organizations are facing problems to build software within establishing time and costs. Organization and process patterns supply proven solutions to recurring software development process. These pattern categories allow reuse in higher abstract levels, that is, in organizational and process levels. However, else than improve and organize the software development process, organizations must speed up that process to attend market demands. Agile development methods such as Scrum and Extreme Programming (XP) are being often utilized due to the proposal of delivering quality software in less time. In that context, this paper proposes an organized form to use organizational and process patterns together with the Scrum agile method, to allow its extension or adaptation according to the needs of the organization that will use it. Based in use experience and using the SPEM metamodel, phases of integration of organizational and process patterns to Scrum have been proposed and used to create a Scrum extension. Scrum, as other agile methods, presents some weak points that need alternatives to improve them. So, using the phases devised, some organization and process patterns have been integrated to Scrum in order to deal with questions not approached by it. The result of a pilot evaluation study conducted to verify the advantages of that integration and of the SPEM modeling, has indicated the convenience to do them. After the application of the integration phases with some patterns and Scrum, the possibility of guidelines creation to integrate organizational and process patterns to other agile methods has been noted.